Listening - Badger, Ian (Tổng hợp, 2014)
Understand what they're saying - however they say it This completely innovative self-study book and audio CD set is the perfect way for busy executives to improve their English listening skills. It features real people talking about their work and their lives in a variety of native and non-native accents alongside exercises and learning material.